The Impact of Human Right on Royalty Restrictions in Intellectual Property - Citra , Made Emy Andayani (Lembaga Contrarius Indonesia, 2026)
The limitation of royalties within the intellectual property regime gives rise to tension between the protection of creators’ exclusive rights and the fulfillment of public interests, particularly from a human rights perspective. This study aims to analyze the ontological dimension of royalty limitations and their implications for human rights.The research questions addressed in this study concern the ontological nature of royalty limitations and their implications for the balance between intellectual property rights and human rights. This research employs a normative legal research method, utilizing statutory, conceptual, and philosophical approaches. The findings indicate that royalty limitations constitute an inherent aspect of intellectual property rights, which are non-absolute in nature and embody a social function. Such limitations play a significant role in expanding public access to healthcare, education, and knowledge; however, they may also diminish the protection of creators’ economic rights if not regulated proportionately. Accordingly, regulatory frameworks emphasizing the principles of proportionality and the balancing of interests are required to achieve harmonization between the protection of intellectual property and the fulfillment of human rights.